2021
DOI: 10.1111/efp.12672
|View full text |Cite
|
Sign up to set email alerts
|

Blue‐stain fungi isolated from freshly felled Scots pine logs in Poland, including Leptographium sosnaicola sp. nov

Abstract: Scots pine (Pinus sylvestris L.) is a conifer tree native to Eurasia. Due to optimal climatic and site conditions, this pine occurs in 58% of forested areas in Poland and is thus the most economically important timber species throughout the country (GUS, 2018). However, there are many challenges associated with the harvesting and use of Scots pine timber, such as rotting and staining by microorganisms.The large proportion of sapwood in Scots pine stems is reported to be very susceptible to blue-stain (Seifert,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…The authors showed that L. sosnaicola formed a monophyletic line within other members of Leptographium , and its morphology did not resemble any known Leptographium species. Our results also show L. sosnaicola L2.6 within L. lundburgii complex and totally separated from the other sister species, corroborating the previous observations (Jankowiak et al, 2021 ). The other Leptographium species identified L. terebrantis , firstly described as associated with the black turpentine beetle Dendroctonus terebrans (Barras and Perry, 1971 ), was reported as pathogen of woody roots and recently related to crown symptoms and tree mortality in P. taeda (Mensah et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The authors showed that L. sosnaicola formed a monophyletic line within other members of Leptographium , and its morphology did not resemble any known Leptographium species. Our results also show L. sosnaicola L2.6 within L. lundburgii complex and totally separated from the other sister species, corroborating the previous observations (Jankowiak et al, 2021 ). The other Leptographium species identified L. terebrantis , firstly described as associated with the black turpentine beetle Dendroctonus terebrans (Barras and Perry, 1971 ), was reported as pathogen of woody roots and recently related to crown symptoms and tree mortality in P. taeda (Mensah et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…As suggested by Wang et al ( 2018 ), the dominance of O. ips can have either an indigenous origin or be an effective adaptation to local pine forests. In fact, the presence of O. ips in non-infected trees in Seia could be explained by natural infection with various species of bark beetles as is common in European pine forests (Chang et al, 2017 ; Jankowiak et al, 2021 ). The other ophiostomatoid isolates were Leptographium sp., Graphilbum sp., and Sporothrix sp., which were also described in other studies (Zhao et al, 2013 , 2018 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not all ophiostomatoid fungi are responsible for tree mortality, many are well recognized as the causal agents of blue stain (sap stain) in the wood of economically important tree hosts (Kirisits 2004;Seifert et al 2013). This is particularly true for pine (Pinus) plantations globally (Seifert et al 2013;de Errasti et al 2018;Jankowiak et al 2021). Systematic surveys of bark beetles and ophiostomatoid fungi associated with pine have been completed in North and Central America (Zhou et al 2004a;Kim et al 2011;Klepzig and Hofstetter 2011;Taerum et al 2013;Marincowitz et al 2020), Europe (Linnakoski et al 2012;Romón et al 2014;Jankowiak et al 2012Jankowiak et al , 2020, Asia (Zhou et al 2013;Masuya et al 2013;Kirisits et al 2013), with a significant number of surveys conducted recently in China (Chang et al 2017(Chang et al , 2019Wang et al 2018Wang et al , 2019Wang et al , 2020, South America (Zhou et al 2004b;de Errasti et al 2018) and New Zealand (Thwaites et al 2005(Thwaites et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Description of these new species brings the total number of species in this genus to 62, of which 16 occur in Poland. These include the six species described here as well as S. aurorae (Jankowiak et al 2019b), S. cantabriensis (Jankowiak et al 2017), S. dentifunda (Aghayeva et al 2005, Jankowiak et al 2019b, S. eucastaneae (Jankowiak et al 2019a(Jankowiak et al , 2019b(Jankowiak et al , 2021, S. fusiformis (Jankowiak et al 2019a(Jankowiak et al , 2019b, S. inflata (Jankowiak et al 2012;Bilański 2013a, 2013b), S. inflata '2' (Jankowiak et al 2019a(Jankowiak et al , 2019b, S. prolifera (Kowalski and Butin 1989;Jankowiak et al 2019aJankowiak et al , 2019b, S. stenoceras, (Kowalski and Butin 1989;Bilański 2013b, Jankowiak et al 2019b) and S. variecibatus (Jankowiak and Bilański 2013b). All of the species described in this study are morphologically similar, having asexual states with hyaline or lightly pigmented conidia produced holoblastically on denticulate conidiogenous cells or directly from the hyphae.…”
Section: Discussionmentioning
confidence: 99%